Transduction of a human RNA sequence by poliovirus. - Charini, W A (1994)
Cells infected with poliovirus express a virally encoded polyprotein which undergoes self-mediated cleavage into structural and nonstructural viral proteins. Most of these cleavages are catalyzed by the 3C proteolytic domain of the polyprotein. Polyprotein synthesized in vitro from an RNA template containing a three-nucleotide insertion in 3C underwent proteolytic processing at all but one of the 3C-dependent cleavage sites. When transfected into HeLa cells, this RNA template displayed a lethal phenotype. We report here the isolation of two pseudorevertant progeny strains with restored protein-processing phenotypes, one of which appears to have arisen by transduction of a stretch of nucleotides from human 28S rRNA.